Aesthetic assumptions and theoretical precursors of Visual Studies in the Anglo-Saxon field - Murcia Serrano, Inmaculada (Escritura e Imagen, 2022)
Already highly developed in the contemporary academic outlook, Visual Studies possess a brief but intense tradition in which some works have proved to be decisive. Rather than examining the philosophical premises on which this new discipline is based, we study here the texts of the main precursors of image studies in the Anglo-Saxon field, with the aim of showing the fundamental assumptions and the historical precedent on which their theories have been based. The works of Berger, Bryson, Lowe and Mitchell are chosen as the most representative.